2019
DOI: 10.1253/circj.cj-19-0552
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Out-of-Hospital Cardiac Arrest in Aged Individuals in Relation to Cold Ambient Temperature ― A Report From North Tochigi Experience ―

Abstract: A nnually, out-of-hospital cardiac arrest (OHCA) occurs in over 120,000 individuals in Japan, and approximately 80% of these occur indoors. 1 Moreover, in approximately 70% of OHCA the subject is an elderly individual over 70 years old, and the survival rate with favorable neurological outcome is low. 1 Recently, an association between atmospheric conditions and the occurrence of OHCA was reported. 2 Furthermore, previous study has reported a relationship between colder temperature and the development of myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
(8 reference statements)
1
10
0
Order By: Relevance
“…Our SHAP analysis revealed that the major factors affecting OHCA incidence were low mean ambient temperature, the diurnal temperature of the previous day, month, percentage of the elderly population, and the day of the week. The result showing the link between low average temperature in the winter season and high OHCA incidence is in line with that reported in previous studies [16][17][18]. Even though exposure to cold weather was a major factor in the seasonality of OHCA incidence, the incidence peaked in January rather than February, in which the average temperature was the lowest of the year.…”
Section: Discussionsupporting
confidence: 91%
“…Our SHAP analysis revealed that the major factors affecting OHCA incidence were low mean ambient temperature, the diurnal temperature of the previous day, month, percentage of the elderly population, and the day of the week. The result showing the link between low average temperature in the winter season and high OHCA incidence is in line with that reported in previous studies [16][17][18]. Even though exposure to cold weather was a major factor in the seasonality of OHCA incidence, the incidence peaked in January rather than February, in which the average temperature was the lowest of the year.…”
Section: Discussionsupporting
confidence: 91%
“…Other designs included case-crossover studies, a prospective observational study, a cross-sectional study and an ecological time series study . The method of statistical analysis varied with the study design.…”
Section: Resultsmentioning
confidence: 99%
“…The spatial setting of the studies covered differing levels, ranging from suburban to urban ,, and regional ,, to national , providing information on the effects of temperature in different climatic areas.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations